PELANGGARAN PRINSIP KERJA SAMA DALAM LOMBA DEBAT TINGKAT SMA SE-DERAJAT PADA KEGIATAN PRAKTIKUM SASTRA KE-25 - Azaky, Andri; Elmustian, Elmustian; Charlina, Charlina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research aims to find a violation and the causes of the violations of what are included in the equivalent of the high school-level debate on the activities of the 25th Literary Practice. This type of research is qualitative with a descriptive method. The data was obtained by the technique of recording video of the race and then transcribed into a writing form. The data was then analyzed by identifying violations in the video of the debate that had been transcribed in written form. These research data in the form of violation of the principle of cooperation that violate violations of the quantity rule, maxim of quality, maxime of relevance, and the maxim of manners. Based on the data analysis that was done, the authors found sixteen causes of the violation of the principle of cooperation are the maxime of quantity, quality, relevance, and how, are as follows: 1) factor clarification of the information, 2 ) factors, 3) change factors of topic, 4) factors that relate to a case 5) factors implicitly make others, 6) the factors you want to look friendly, 7) factors that are expressed fear and haste, 8) factors , one of diction and language rules, 9) factors that lack the use of language, 10) factors or lack of concentration, 11) factors ignorance of facts, 12) factors, lack of information, 13) factors lead facts to the argument to strengthen, 14) factors do not understand the context, 15) factors failed the time well, 16) volatility emotions. Of the sixteen factors, four of which are the purpose of Tri-Thesis (2015). The rest is a new factor that emerged in this study.Keywords: principles of cooperation, debate about competition, literary practice